2014
DOI: 10.1016/j.nutres.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Total dietary fiber intakes in the US population are related to whole grain consumption: results from the National Health and Nutrition Examination Survey 2009 to 2010

Abstract: Whole grain (WG) foods have been shown to reduce chronic disease risk and overweight. Total dietary fiber is associated with WG and its health benefits. The purpose was to determine whether associations exist between WG intake (no-WG intake, 0 ounce equivalent [oz eq]; low, >0-<3 oz eq; high, ≥3 oz eq) and total dietary fiber intake among Americans 2 years and older. One-day food intake data from the US National Health and Nutrition Examination Survey 2009 to 2010 (n = 9042) showed that only 2.9% and 7.7% of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 34 publications
13
87
0
Order By: Relevance
“…Most adolescents usually consume an insufficient quantity of dietary fibre, despite positive reports on the impact of fibre on health (2,11,12). Insufficient dietary fibre intake is a result of decreasing consumption of fruit and vegetables in adolescents (13).…”
Section: Introductionmentioning
confidence: 99%
“…Most adolescents usually consume an insufficient quantity of dietary fibre, despite positive reports on the impact of fibre on health (2,11,12). Insufficient dietary fibre intake is a result of decreasing consumption of fruit and vegetables in adolescents (13).…”
Section: Introductionmentioning
confidence: 99%
“…The 2010 Dietary Guidelines for Americans call for a reduction in the number of servings of refined grains and consumption of at least half of total grains as whole grains (2) . However, 2009-2010 National Health and Nutrition Examination Survey (NHANES) data show that only 2·9 % of children/adolescents (2-18 years) consume the recommended three daily whole grain ounceequivalents, while 38·8 % consume no whole grains (3) . Pizza is a popular food commonly consumed by children and adolescents.…”
mentioning
confidence: 99%
“…As cereal fibre appears to be a significant factor in 377 total dietary fibre intakes, encouragement of higher fibre cereal foods may be a key target to 378 increasing intake of total dietary fibre among Australians. This is supported by a previous 379 study by Reicks et al (2014), which found that whole grain, high fibre cereal foods made a 380 significant contribution to total dietary fibre intake in adults and children. …”
mentioning
confidence: 57%